2018
DOI: 10.1038/s41598-018-21702-5
|View full text |Cite
|
Sign up to set email alerts
|

Poly(butylene succinate)/bamboo powder blends as solid-phase carbon source and biofilm carrier for denitrifying biofilters treating wastewater from recirculating aquaculture system

Abstract: In this study, Poly(butylene succinate)/bamboo powder (PBS/BP) was newly applied and tested for 8 months as the carbon source in two moving bed reactors for nitrate removal in real RAS wastewater (fresh/sea water), with the purposes of simultaneous reducing the cost of PBS packing and effluent DOC. Fast start-ups were obtained in both reactors, in which high denitrification rates were observed (0.68 ± 0.03 and 0.83 ± 0.11 kg -N m−3 d−1 for fresh and sea water, respectively) with no nitrite and low ammonia accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A lot of effort [ 4 , 10 , 21 , 22 , 23 ] has been dedicated to the fabrication of PBS/natural fiber biocomposites. Various natural lignocellulosic fibers such as ramie [ 21 ], jute fiber [ 4 ], bamboo fiber [ 22 ], and sisal fiber [ 23 ], to mention a few, have been added into the PBS matrix in order to improve the properties of the resultant biocomposites. This review paper discusses the preparation, morphology, modification, and mechanical properties of PBS/natural fiber biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of effort [ 4 , 10 , 21 , 22 , 23 ] has been dedicated to the fabrication of PBS/natural fiber biocomposites. Various natural lignocellulosic fibers such as ramie [ 21 ], jute fiber [ 4 ], bamboo fiber [ 22 ], and sisal fiber [ 23 ], to mention a few, have been added into the PBS matrix in order to improve the properties of the resultant biocomposites. This review paper discusses the preparation, morphology, modification, and mechanical properties of PBS/natural fiber biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the COD Cr concentration in the effluent of Reactor 2 was kept at a low level during the whole process, while the COD Cr concentration in the effluent of Reactor 1 had a negative relationship with the influent nitrate concentration (Figure 8d). Previous studies showed that the biological degradation of solid carbon source and denitrification are two independent processes [41]. Therefore, the high/low COD Cr concentration at low/high influent nitrate (16.1 and 30.8 mg/L) could possibly be explained by the continuous degradation without/with full utilization of denitrifying bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon source additions in BFT systems seem to greatly affect the concentration of this compound. For example, by increasing the C/N ratio in a BFT system to 20 using glucose as the extra carbon material, Liu et al (2018a) found that NO À 2 was almost always at very low concentrations (<0.2 mg L −1 ) and sometimes not even detected (0 mg L −1 ) in an O. niloticus-based culture. Additionally, using rice bran, glycerol and sucrose as extra carbon sources, Dauda et al (2017) observed that nitrite-N was significantly lower in all carbon-supplemented groups compared with that in the control group in which there was no carbon addition.…”
Section: Dissolved Inorganic Nitrogenmentioning
confidence: 99%